How and why planners make traffic-increasing plans - and what could be done to change the situation. - Tennøy, Aud (My University, 2013)
Land use and transport-systems are continuously being developed in ways that cause growth in traffic volumes. In order to be able to change this situation, it is necessary to know what causes it. Instead of studying politicians, the public, or the planning system, the question asked in this paper is how and why planners make plans which, if implemented, cause growth in traffic volumes. The explanatory factors studied are the expert knowledge, the planners and the plan-making processes. It was found that even if the expert knowledge is good enough to guide planners aiming at making traffic-reducing plans, it needs to be improved with respect to accessible and applicable descriptions of theoretical and empirical knowledge, as well as of methods. Further, the planners need to be more knowledgeable if the current situation is to be changed. Regarding the plan-making processes, the planners need to ensure that this objective is clearly stated in overall plans and emphasised in operational plans, that the politicians are made aware of traffic-increasing consequences of proposed projects and given alternative options, and that faulty and biased assessments and analyses are disclosed. There is large room for improvement for planners and for planning researchers.
Keywords: Verkehrsplanung; Planungstheorie; Planungsprozess; Wirkungsanalyse; Planerausbildung; Verkehrsaufkommen; Verkehrswende; Verkehrsreduzierung